2010
DOI: 10.1158/0008-5472.can-10-2840
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Control of the ERBB2 Amplicon by ERRα and PGC-1β Promotes Mammary Gland Tumorigenesis

Abstract: Overexpression of ERBB2 and its neighboring genes on chromosome 17 occurs in approximately 25% of breast tumors and is associated with poor prognosis. While amplification of the 17q12-21 chromosomal region often correlates with an increase in the transcriptional rates of the locus, the molecular mechanisms and the factors involved in the coordinated expression of genes residing within the ERBB2 amplicon remain largely unknown. Here we demonstrate that estrogen-related receptor a (ERRa, NR3B1) and its coregulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 48 publications
5
71
0
1
Order By: Relevance
“…Although we could not detect recruitment of b-catenin to the ERBB2 proximal promoter, we detected a 3-fold enrichment in b-catenin and a 20-fold enrichment in RNA polymerase II recruitment to an intronic ERBB2 site (Fig. 7D), which has been shown to be bound by several factors that are important in the transcriptional regulation of ERBB2 (18,38). b-Catenin and RNA polymerase II occupancy to this site was further enriched upon treatment with the Wnt3 ligand (Fig.…”
Section: /Ermentioning
confidence: 70%
See 1 more Smart Citation
“…Although we could not detect recruitment of b-catenin to the ERBB2 proximal promoter, we detected a 3-fold enrichment in b-catenin and a 20-fold enrichment in RNA polymerase II recruitment to an intronic ERBB2 site (Fig. 7D), which has been shown to be bound by several factors that are important in the transcriptional regulation of ERBB2 (18,38). b-Catenin and RNA polymerase II occupancy to this site was further enriched upon treatment with the Wnt3 ligand (Fig.…”
Section: /Ermentioning
confidence: 70%
“…We found recruitment of b-catenin and RNA polymerase II at an intronic ERBB2 site, which was further enhanced upon Wnt3 exposure, whereas ICG-001 treatment disrupted RNA polymerase II occupancy at this site. This site is particularly important as transcription factors such as ERRa and ER-a have been shown to compete for binding to this site to activate or repress ERBB2 transcription (18,38). In addition, recent data have established that ERRa, b-catenin, and Lef1 form a transcriptionally active complex to activate gene expression (53).…”
Section: Discussionmentioning
confidence: 99%
“…All three ESRR isoforms were identified as coactivating Review t b doan and others Nuclear receptors in breast cancer factors of HIF and to enhance HIF-induced glycolytic and angiogenic gene expression in hypoxic condition (Ao et al 2008). ESRRA also regulates the expression of ERRB2 (Deblois et al 2010), which was reported to translocate to the mitochondria of tumor cells and regulate energy metabolism. Overexpression of mitochondrial ERBB2 decreases mitochondrial electron transport chain activity and enhances cellular glycolysis (Ding et al 2012).…”
Section: Estrogen-related Receptors (Errs)mentioning
confidence: 97%
“…This is consistent with recent findings that PGC1β promotes tumorigenesis in many tissues through the PGC1/ERR signaling axis (Deblois et al ., 2010, 2013; Eichner et al ., 2010). In this study, we show that LDHA is upregulated by the PGC1β/RXRβ signaling pathway and partly contributes to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PGC1β is upregulated in cancer cells and promotes tumorigenesis by regulation of mitochondrial biogenesis and glycolysis metabolism (Bellafante et al ., 2014; Chang et al ., 2011; Deblois et al ., 2010; Deblois et al ., 2013), while the detailed mechanism still needs to be fully understood.…”
Section: Introductionmentioning
confidence: 99%